Construction of Islamic Education Based on Islamic Boarding Schools: A Case Study at Al-Manar Muhammadiyah Modern Islamic Boarding School in South Sumatra - Firmansyah; Muhammad Aufal Minan; Adriansyah. NZ; Afiq Fikri Almas; Ivan Riyadi; Thoriq Tri Prabowo (Jurnal Pendidikan Agama Islam, 2025)
Purpose – This study aims to analyse the implementation of traditional Islamic boarding school-based education at Al-Manar Muhammadiyah Modern Islamic Boarding School, South Sumatra. The background of this study is the need for a character education model that not only focuses on academic aspects but also on the moral and spiritual. development of students through a boarding school-specific approach Design/methods/approach – This study uses a qualitative approach with a case study approach, data collection techniques using observation, in-depth interviews, and documentation in the field for twelve months. Findings – The results of the study show that adab education at Al-Manar Islamic Boarding School is internalised through three main stages, namely value transformation, value transaction, and value transinternalisation. This process is reinforced by lectures, role modelling, practice and habituation, and a reward and punishment system, which collectively shape the religious, social, and personal character of the students. Supporting factors for the implementation of adab education include the exemplary behavior of the ustaz, a structured student development system, the involvement of all components of the pesantren, strict rules and regulations, and a conducive religious social environment. The study also found obstacles to implementation, such as low intrinsic motivation among students and the influence of global culture. Research implications/limitations – The implications of this study indicate that a tradition-based approach to education can be an alternative model for holistic character building. Originality/value – This study recommends strengthening reflective and participatory methods in the internalization of adab values, as well as the need to replicate this model in other Islamic educational institutions to address the challenges of character education for students in the era of globalization